Just One More Moment (Kingston Family, ,, 2024)
She thinks happily ever after only happens in romance novels. He can't wait to prove her wrong... Falling in love is not on Raven Walsh's agenda. Running from her past keeps her way too busy for that. She can, however, handle a friends-with-benefits scenario with the hot billionaire who co-owns The Back Door bar. But trusting him with her heart? Not a chance... Remington Sterling has had his eye on the smart and sexy Raven since she started waitressing at his bar. He knows she's gun-shy where relationships are concerned. But he's ready to do whatever it takes to convince her he's worth the risk... When Raven's secrets catch up to her in a big way, she must decide if the potential cost of trusting Remy is more than she's willing to pay—and Remy will need to figure out how far he's willing to go for love... Just One More Moment, book 1 in the Sterling Family series (all can be read as standalones), is a spicy contemporary romance featuring a ready-to-run heroine and the possessive, protective alpha hero who is more than ready to catch her. Meet The Sterling Family, a continuation of Carly Phillips' bestselling Kingston Family Series of sizzling stand-aloneromances. The Kingston Family Series (every book stands alone) 1. Just One Night (The Kingston Family) 2. Just One Scandal (The Kingston Family) 3. Just One Chance (The Kingston Family) 4. Just One Spark (The Kingston Family) 5. Just One Dare (The Dirty Dares) 6. Just One Kiss (The Dirty Dares) 7. Just One Taste (The Dirty Dares) 8. Just Another Spark short story (The Kingston Family) 9. Just One Fling (The Dirty Dares) 10. Just One Tease (The Dirty Dares) The Sterling Family 1. Just One More Moment ​​​​​​​2. Just One More Dare